Scattering analyses of arbitrary roughness from 2-D perfectly conductive periodic surfaces with moments method - Yamac, Yunus Emre; Kizilay, Ahmet (Tubitak Scientific & Technological Research Council Turkey, 2022)
In this paper, a periodic-MoM-based code with high accuracy performance is developed to calculate electromagnetic scattering from a periodic conductive surface in two dimensions with any degree of roughness. Firstly, the existing separate methods in the literature are reviewed step by step to compose a periodic-MoM solution for 2-D periodic surfaces. Then, the dynamic selection of optimal formulation of the periodic-MoM solutions created using these existing methods is evaluated to reduce solution time and obtain high accuracy. In this study, the performance parameters of the existing methods are investigated in solving a real 3-D scattering problem by a periodic-MoM for the first time in the literature. Eventually, a commercial EM solver with a similar numerical approach is employed for comparison, validation, and accuracy achievements of these different periodic-MoM formulations. Furthermore, an analytical solution named Floquet mode-matching method (FMMM) is developed based on the Rayleigh hypothesis for slightly rough surfaces, and the accuracy of the code is tested using this analytical solution. This study is entirely compatible with analytical solutions and gives better results than this commercial EM solver in terms of accuracy. Also, the FMMM formulation derived for comparison provides a more straightforward solution than the small perturbation method (SPM), a classical solution method, and it is adapted to two-dimensional surface roughness for the first time in this paper. However, this full-wave solution has no restriction on surface roughness, unlike the analytical solutions.
Keywords: FMMM; MoM; periodic rough surfaces; PGF; SPM; LINEAR SOURCE DISTRIBUTIONS; GREENS-FUNCTION; ELECTROMAGNETIC-WAVES; NUMERICAL EVALUATION; POTENTIAL INTEGRALS; SINGULARITY; QUADRATURE; Computer Science; Engineering